The Influence of Interactivity, Trust, and Online Customer Reviews on Impulse Buying of Avoskin Products on Shopee: a Study of Generation Z in Surabaya - Siti Chalyandrha Putry; Acep Samsudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine how interactions, trust, and online customer reviews influence impulsive purchasing of Avoskin products among Generation Z in Surabaya. This study employs the Stimulus-Organism-Response (S-O-R) theory, which explains that environmental influences can affect a person’s internal state, subsequently leading to specific actions or behaviors. The methodology used was a quantitative study involving 156 participants selected through purposive sampling. Research data were collected and analyzed using multiple linear regression with SPSS version 31. The results indicate that interaction, trust, and customer reviews collectively influence impulsive purchases of Avoskin products among Generation Z consumers in Surabaya. Partial tests also revealed that all three independent variables have a positive and significant impact on impulsive purchasing. Among these three variables, the trust variable had the greatest influence, with a regression coefficient of 0.426. Furthermore, the coefficient of determination of 71.4% indicates that changes in impulsive purchasing behavior can be explained by the three independent variables in this study, while the remaining portion is influenced by other factors outside the model under investigation.